Beyond the label : women, leadership, and success on our own terms - Chiquet, Maureen (New York, NY : HarperBusiness, an imprint of HarperCollinsPublishers, 2017)
The former global CEO of Chanel traces her unlikely journey to a business leader, offering advice on how to move beyond the confines of staid expectations while discovering personal goals, strengths, and leadership values that can enable a career on one's own terms.
Breathing deeply -- With fresh eyes -- Yielding to chance -- Road training -- Finding your groove -- A fine line -- Making your mark -- Taking charge -- Having it all -- Soul calling -- Embracing paradox -- Cutting the corset.
Keywords: Women executives; Leadership; Executive ability; Success in business; Leadership; Women executives; Success in business; Executive ability; Executive ability; Leadership; Success in business; Women executives